Rural sixth-grade teachers’ and students’ perceptions of a mindfulness-based mental health curriculum - Folger, Austin; Nekkanti, Akhila; Williamson, Gina; Guidinger, Claire; Kelly, Nichole R. (Frontiers in Psychology, 2023)
Introduction Mindfulness-based interventions (MBIs) have the potential to improve students’ mood, behavior and cognitive functioning; yet, little is known about the feasibility and acceptability of adapting such programs for rural middle schools. Methods An exploratory qualitative evaluation was conducted to examine the feasibility and acceptability of an initial trial delivery of AttuneEd®, a trauma-informed, mindfulness-based mental health curriculum. In this single-group design study, 10 weekly lessons were taught in a middle school located in a rural town in the pacific northwest during 6th grade students’ P.E. classes. Three P.E. teachers, 26 6th grade teachers, and one school counselor attended trainings before and mid-curriculum implementation, where they provided qualitative feedback. A total of 160 students completed acceptability surveys before and after curriculum delivery. Results Three themes were identified from qualitative data: cultural considerations, teacher self-efficacy, and barriers and facilitators to student acceptability. Student acceptability ratings were high. Students reported, on average, that the classes helped them better understand themselves and others. Conclusion Some identified needs for future MBIs include (1) the need for culturally sensitive, trauma-informed delivery strategies; (2) teachers’ desire for more support in content delivery; and (3) students’ desire to have their own teachers deliver the curriculum. Findings elucidate the nuances associated with implementing an MBI in a rural middle school and have notable implications for development, scalability, and sustainability.